Meningkatkan Aksesibilitas dan Konsistensi Desain Web: Studi Implementasi di Figma - Rina, Rina; Anisa, Nor (Majalah Ilmiah METHODA, 2025)
In this ever-evolving digital era, technology, especially User Interface (UI) and User Experience (UX) design, plays a crucial role in enhancing user comfort while interacting with applications and websites. As a cloud-based design tool, Figma simplifies the creation of consistent and accessible designs while enabling real-time collaboration among designers. Through user experience testing and analysis, this study aims to determine Figma’s role in improving web design accessibility and consistency. The research was conducted through Black Box testing and the distribution of a questionnaire, with 18 respondents participating. The test results indicate that Figma’s design is easy to understand and contains many consistent elements. However, there are some areas for improvement, particularly related to navigation and feature search. Overall, 33.3% of respondents rated Figma’s web design as excellent in terms of accessibility and consistency, although there is room for further improvement. This study suggests enhancing navigation aspects and ensuring design elements are more consistent across pages to improve the overall user experience.